2008
DOI: 10.14411/eje.2008.075
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich fibroin gene of the Japanese wild silkmoth, Rhodinia fugax (Lepidoptera: Saturniidae)

Abstract: Abstract. We cloned and characterized a partial fibroin gene of Rhodinia fugax (Saturniidae). The gene encodes a fibroin consisting mainly of orderly arranged repeats, each of which is divided into a polyalanine and a nonpolyalanine block, similar to the fibroins of Antheraea pernyi and A. yamamai. Three repeat types differ in the sequence of the nonpolyalanine block. In contrast to the Antheraea fibroins, the fibroin of R. fugax is rich in glutamate and leucine residues (about 3% and 5%, respectively) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The composition of amino acids after polyalanin a repetition consists of the amino acid glycine (G) and serine (S). The amino acid arrangement like that, was similar with amino acid sequence of second exon fi broin of Saturniidae family (Da a et al, 2001b;Sezutsu et al, 2010 ). There are four type of polyalanine sequence motif in second exon fibroin A. pernyi (Sezutsu & Yukuhiro, 2000;Sezutsu, et al, 2009), while repetitive GAGASG pa ern was founded in B. mori (Zhou et al, 2000).…”
Section: Diff Erent Motifmentioning
confidence: 53%
See 4 more Smart Citations
“…The composition of amino acids after polyalanin a repetition consists of the amino acid glycine (G) and serine (S). The amino acid arrangement like that, was similar with amino acid sequence of second exon fi broin of Saturniidae family (Da a et al, 2001b;Sezutsu et al, 2010 ). There are four type of polyalanine sequence motif in second exon fibroin A. pernyi (Sezutsu & Yukuhiro, 2000;Sezutsu, et al, 2009), while repetitive GAGASG pa ern was founded in B. mori (Zhou et al, 2000).…”
Section: Diff Erent Motifmentioning
confidence: 53%
“…acid alanine has the highest frequency among 3 triplet codons for amino acid alanine, i.e (GCA, GCT, GCG, GCC, with a frequency of consecutive 49, 17, 16, 1 times respectively). This result indicated that the composition of the nucleotide was similar, but their size was heterogeneous, such as the second exon of other Lepidoptera (Craigh & Riekel, 2002;Sezutsu et al, 2010) Many Repetitif Alanine Amino Acid with…”
Section: E E D P T G H E R I F E E D D I I K R V G a A A A S S A A A mentioning
confidence: 95%
See 3 more Smart Citations